The predictive roles of social safeness and flourishing on problematic Facebook use - Uysal, Recep (SAGE PUBLICATIONS LTD, 2015)
Social networking sites like Facebook, Twitter, and Foursquare have become an integral part of human life, and their use has increased considerably over recent years. Facebook is the fastest growing social networking site, but little research has investigated the negative outcomes relating to the problematic use and predictors of this media phenomenon. This study examined the predictive roles of social safeness and flourishing on problematic Facebook use. The study was carried out among 229 Turkish university students (120 women, 109 men, M-age=20.41years, standard deviation=1.64, and age range=18-27). The participants completed the Turkish version of the Bergen Facebook Addiction Scale, the Social Safeness and Pleasure Scale, and the Flourishing Scale. The research data were analyzed by correlation and multiple regression analyses. Problematic Facebook use was correlated negatively with social safeness and flourishing. In addition, the findings indicated that social safeness and flourishing were significant predictors of problematic Facebook use. The results were discussed in light of relevant literature.
Keywords: Flourishing; problematic Facebook use; social safeness; COLLEGE-STUDENTS; MENTAL-HEALTH; NETWORK SITES; INTERNET USE; ADDICTION; SATISFACTION; GENDER; MODEL; LIFE; Psychology